Risk-Adapted Postmastectomy Radiotherapy Decision Based on Prognostic Nomogram for pT1-2N1M0 Breast Cancer: A Multicenter Study - Li, Ming; Yue, Jinbo; Wan, Xiangbo; Hua, Bin; Yang, Qiuan; Yang, Pei; Zhang, Zijian; Pei, Qian; Han, Weidong; Xu, Yaping; Xia, Xuefeng (Frontiers in Oncology, 2020)
Purpose: The aim of this study was to develop a widely accepted prognostic nomogram and establish a risk-adapted PMRT strategy based on locoregional recurrence for pT1-2N1M0 breast cancer. Methods and Materials: A total of 3033 patients with pT1-2N1M0 breast cancer treated at 6 participating institutions were retrospectively reviewed between 2000 and 2016. A nomogram was developed to predicted locoregional recurrence-free survival (LRFS). A propensity score-matched (PSM) analyses was performed in risk-adapted model. Results: With the median follow-up of 65.0 months, the 5-year overall survival (OS), disease free survival (DFS) and LRFS were 93.0%, 84.8% and 93.6%, respectively. There was no significant difference between patients who received PMRT or not for the entire group. A nomogram was developed and validated to estimate the probability of 5-year LRFS based on five independent factors including age, primary tumor site, positive lymph nodes number, pathological T stage and molecular subtype that were selected by a multivariate analysis of patients who did not receive PMRT in the primary cohort. According to the total nomogram risk scores, the entire patients were classified into low- (40.0%), moderate- (42.4%) and high-risk group (17.6%). The 5-year outcomes were significantly different among these three groups (P＜0.001). In low-risk group, patients who received PMRT or not both achieved a favorable OS, DFS and LRFS. In moderate-risk group, no differences in OS, DFS and LRFS were observed between PMRT and no PMRT patients. In high-risk group, compared with no PMRT, PMRT resulted in significantly different OS (86.8% vs 83.9%, P= 0.050), DFS (77.2% vs 70.9%, P= 0.049) and LRFS (90.8% vs. 81.6%, P= 0.003). After PSM adjustment, there were no significant differences in OS, DFS and LRFS in low-risk and moderate-risk groups. However, in the high-risk group, PMRT still resulted in significantly better OS, DFS and improved LRFS. Conclusions: The proposed nomogram provides an individualized risk estimate of LRFS in patients with pT1-2N1M0 breast cancer. Risk-adapted PMRT for high-risk patients is a viable effective strategy.